2015
DOI: 10.1161/circheartfailure.114.001503
|View full text |Cite
|
Sign up to set email alerts
|

Survival and Neurocognitive Outcomes After Cardiac Extracorporeal Life Support in Children Less Than 5 Years of Age

Abstract: Background— Survival after pediatric cardiac extracorporeal life support (ECLS) is guarded, and neurological morbidity varies widely. Our objective is to report our 10-year experience with cardiac ECLS, including survival and kindergarten entry neurocognitive outcomes; to identify predictors of mortality or adverse neurocognitive outcomes; and to compare 2 eras, before and after 2005. Methods and Results— From 2000 to 2009, 98 children ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 28 publications
1
27
0
3
Order By: Relevance
“…After cardiac ECMO, neurologic outcomes with comprehensive follow-up suggest mental delay in 38% of survivors and no clear difference with E-CPR, but this is based on very small numbers [3]. Recently, the CPTFP reported a review of 10 years of cardiac ECMO in 98 patients and found 65% survival to hospital discharge, 51% survival to 5 years, full-scale intelligence quotient of survivors 79.7 (SD 16.6) with 25% below 2 SD of the population mean, and GAC of 79.2 (SD 19.4); E-CPR and location of cannulation (operating room vs. PCICU) were not associated with survival or neurocognitive outcomes [18]. Of interest, survival improved in the more recent era, and this was associated with lower lactate and inotrope scores prior to ECMO cannulation [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After cardiac ECMO, neurologic outcomes with comprehensive follow-up suggest mental delay in 38% of survivors and no clear difference with E-CPR, but this is based on very small numbers [3]. Recently, the CPTFP reported a review of 10 years of cardiac ECMO in 98 patients and found 65% survival to hospital discharge, 51% survival to 5 years, full-scale intelligence quotient of survivors 79.7 (SD 16.6) with 25% below 2 SD of the population mean, and GAC of 79.2 (SD 19.4); E-CPR and location of cannulation (operating room vs. PCICU) were not associated with survival or neurocognitive outcomes [18]. Of interest, survival improved in the more recent era, and this was associated with lower lactate and inotrope scores prior to ECMO cannulation [18].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the CPTFP reported a review of 10 years of cardiac ECMO in 98 patients and found 65% survival to hospital discharge, 51% survival to 5 years, full-scale intelligence quotient of survivors 79.7 (SD 16.6) with 25% below 2 SD of the population mean, and GAC of 79.2 (SD 19.4); E-CPR and location of cannulation (operating room vs. PCICU) were not associated with survival or neurocognitive outcomes [18]. Of interest, survival improved in the more recent era, and this was associated with lower lactate and inotrope scores prior to ECMO cannulation [18]. In 51 cardiac patients having E-CPR, the CPTFP reported 49% survival to hospital discharge, 43% survival to 5 years, full-scale intelligence quotient of survivors 76.5 (SD 15.9), GAC of 74.5 (SD 20.3) with 47% having a score below 2 SD of the population mean, and 24% having both full-scale intelligence quotient and GAC below 2 SD of the population mean, similar findings to those of all cardiac ECMO cases in the 10-year review [19].…”
Section: Discussionmentioning
confidence: 99%
“…STCF-VAD support permits time for decisions to be made about the potential for myocardial recovery and allows for a detailed assessment of end-organ function. ECMO is another option for short-term support for acute cardiopulmonary failure, but survival to hospital discharge remains a challenge, with reports of 32% to 73% in single centers studies [8][9][10][11][12][13] and 40% to 50% for pediatric cardiac ECMO from the Extracorporeal Life Support Organization (ELSO) registry. 14 We have shown from our experience that STCF-VADs are able to support 67% of children to hospital discharge, with successful long-term outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Of eight available studies on long-term neurological outcome in children who needed ECMO for cardiac failure, only four actually performed age-appropriate neuropsychiatric tests ( 73 ). The proportion of children available for follow-up ranged from 26-51% ( 73 ) and the cohorts overlap in two of these studies ( 91 , 92 ). In a Canadian study in four centers, 42 percent of the 98 children requiring VA-ECMO for cardiac disease were neonates and all 44 survivors without chromosomal abnormality were assessed at a mean age of 52 months.…”
Section: Long-term Outcomesmentioning
confidence: 99%
“…In a Canadian study in four centers, 42 percent of the 98 children requiring VA-ECMO for cardiac disease were neonates and all 44 survivors without chromosomal abnormality were assessed at a mean age of 52 months. The mean IQ was 79.7, and 25% of children had an IQ below−2 SD ( 91 ). The same group reported on neurodevelopmental outcomes in a subset of 17 five-year-old ECPR survivors with cardiac disease who were assessed at least 6 months after ECPR.…”
Section: Long-term Outcomesmentioning
confidence: 99%